Muscular Endurance Training: Bridging Gym Practices with Science Recommendations - P. Prieto-Gonzalez; P. Sagat (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
This study investigated the effectiveness of training methodologies for improving muscular endurance in young adult males and whether these practices align with scientific recommendations. A cross-sectional descriptive comparative study was conducted with 115 male participants aged 18 to 26. Data on various training parameters were collected using a self-administered questionnaire. The results indicated that participants exhibited discrepancies in their training practices compared to established scientific recommendations. An important percentage of study participants did not exercise according to the recommended guidelines regarding exercise sequencing, intensity, repetitions, rest periods, and training supervision. Participants who followed the recommendations regarding intensity, sets, repetitions, weekly training frequency, and supervision achieved higher objective accomplishment scores. Thus, there are notable discrepancies between everyday gym practices and scientific recommendations for improving muscular endurance in young adult men. Adherence to current recommendations and professional supervision are essential for maximizing training effectiveness, preventing injuries, and facilitating future adaptations.